Successful Antiviral Treatment with Direct-Acting Antivirals for Hepatitis C Virus Infection during Peritransplant Period in a Kidney Transplant Recipient - Giovanni Varotti; Ferdinando Dodi; Ernesto Paoletti; Andrea Bruno; Iris Fontana (Case Reports in Transplantation)
Introduction. Hepatitis C virus (HCV) infection continues to represent a poor prognostic factor in kidney transplant (KTx) patients. New direct-acting antiviral agents (DAA) have dramatically changed the therapy management for HCV, showing promising results in terms of sustained virologic response. Timing for DAA therapy in HCV positive kidney waitlist patients continues to be controversial, and caution is recommended due to the potential difficult immunosuppressant dose adjustments, particularly in the early posttransplant period. We report a case of a KTx performed during antiviral DAA therapy. Report of Case. Patient was a 44-year-old man suffering from chronic HCV hepatitis associated with end-stage kidney disease (ESRD), waitlisted for a second KTx as a sensitized patient (panel-reactive antibody peak 85%) in March 2019. Four months later, antiviral DAA therapy was started (glecaprevir/pibrentasvir 300 mg/120 mg daily, for 8 weeks). After 30 days, a left kidney was offered and, given the good compatibility, we decided to proceed with KTx without discontinuing the DAA therapy. A standard straightforward kidney transplant was performed. Immunosuppression included thymoglobulin and prednisone for induction and tacrolimus and mycophenolate for maintenance. After a transient delay graft function, creatinine levels progressively decreased. From postoperative day 3, tacrolimus reached target levels and remained stable. No episodes of acute rejection occurred. The 8-week DAA therapy was carried out without interruption. All HCV-RNA level controls resulted undetectable. On postoperative day 15, the patient was discharged and remains in healthy condition with normal renal function and HCV negative after 18 months of follow-up. Discussion. In this case, DAA therapy during the perioperative KTx period was well tolerated and effective. If confirmed, patients should not necessarily be suspended from the waiting list during DAA therapy for HCV eradication.